Pengaruh Kombinasi Terhadap Kekuatan Material Golok Sulangkar Campuran 10% Pegas 90% Baja SS 400 - Dedi Komarudin (Jurnal Teknik Mesin, 2021)
The manufacture of tools such as machetes in Banten is still widely practiced, machetes are produced from a conventional forging process using a hammer by a blacksmith. Working as a blacksmith in the Banten area, especially in the village of the new village of lightning, was passed down from generation to generation as a traditional blacksmith, but over time the machetes produced by traditional blacksmiths began to be replaced by modern ones machete. The traditional golok of Kampung Baru Village, Petir, consists of two types, the regular machete and the sulangkar golok. The material commonly used by blacksmiths to make machetes is a vehicle spring sheet that is no longer used, while for making machetes, a blacksmith usually combines other materials during forging. The purpose of this study was to determine the differences in the mechanical and micro properties of the two types of golok, Banten cultural heritage. The research was carried out from the start of the search for the material, the manufacturing and forging processes and carried out testing. The results of the hardness test show that the value of the spring material is 423.1 HBW, SS 400 steel material 134.18 HBW, combination material or Sulangkar 735.15 HBW then the data results from the tensile test on steel material SS 400, Spring, Combination or Sulangkar are 442.52 MPa, 1334,60 MPa, 522.81 MPa. The results of the data from the impact test on Spring material, SS 400 steel, Combination or Sulangkar, namely 162 J, 34 J, 88 J. The results of automatic microscope testing and Scanning Electron Microscope (SEM) show the surface of the spring, SS 400 steel and combination materials.